2006
DOI: 10.14310/horm.2002.11191
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulin sensitivity in patients with type 2 diabetes mellitus after oral administration of alpha-lipoic acid

Abstract: bAcKGrOUND: Amelioration of insulin resistance could improve both glycaemic control and cardiovascular risk factors in patients with type 2 diabetes mellitus. Alpha-lipoic acid has been shown to improve insulin action after parenteral administration. ObJEctIVE: the aim of the study was to assess the effect of oral administration of alpha-lipoic acid on insulin sensitivity in patients with type 2 diabetes. DEsIGN: twelve patients (mean±sD; age 52.9±9.9 yrs; body mass index 33.9±7.4kg/m 2 ) were treated with ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 22 publications
2
71
1
3
Order By: Relevance
“…There was no significant difference observed between the groups with regards to Fasting plasma glucose, Fasting insulin level or HOMA-IR in contrary to previous findings by Kamenova [39] who found that a 4 weeks oral treatment with ALA, 600 mg twice daily, significantly increased peripheral insulin sensitivity in patients with DM2 to a level almost similar to that of subjects with normal glucose tolerance. When the effect on lipid abnormalities was assessed, results didn't show any advantage for the combination over lipid profile, though the efficacy of ALA on dyslipidemia was different in other studies [40].…”
Section: Discussioncontrasting
confidence: 99%
“…There was no significant difference observed between the groups with regards to Fasting plasma glucose, Fasting insulin level or HOMA-IR in contrary to previous findings by Kamenova [39] who found that a 4 weeks oral treatment with ALA, 600 mg twice daily, significantly increased peripheral insulin sensitivity in patients with DM2 to a level almost similar to that of subjects with normal glucose tolerance. When the effect on lipid abnormalities was assessed, results didn't show any advantage for the combination over lipid profile, though the efficacy of ALA on dyslipidemia was different in other studies [40].…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, ALA exerts a beneficial effect on the vascular abnormalities of diabetes polyneuropathy and leads to an improvement in peripheral nerve function. ALA also increases insulin sensitivity (32). So ALA should be considered as a good choice among pathogenetically oriented treatments of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the oral supplementation ALA (600 mg twice daily for 4 weeks) treatment which increases the plasma insulin sensitivity [34]. According to Packer et al, ALA is capable to scavenge ROS produced during the lipid peroxidation and guards the cell structure against damage.…”
Section: Alpha-lipoic Acidmentioning
confidence: 99%